1979
DOI: 10.1139/v79-057
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between the excited triplet state of ketones and olefins: the role of triplet exciplexes

Abstract: The quenching of triplet acctone in degassed acetorlitrile solution by electron-rich and electron-deficient olefins has been measured by Rash emission technique. With the exception of fumaronitrile, the efficiency of quenching of triplet ketones by olefins is not determined by the triplet energy of the ketone, but by the ability of the excited ketone to donate or accept electrons. The results are consistent with the assu~nption that back dissociation of the triplet exciplex is an important process in the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…The quenching rates for these sensitizers are higher than the nonelectron donating sensitizers with the same or even higher E,'S. Such phenomenon has also been observed earlier by other workers (6,7). The faster quenching rates are probably due to charge-transfer from the excited donors (sensitizers) to the ground state acceptors.…”
Section: Resultssupporting
confidence: 80%
“…The quenching rates for these sensitizers are higher than the nonelectron donating sensitizers with the same or even higher E,'S. Such phenomenon has also been observed earlier by other workers (6,7). The faster quenching rates are probably due to charge-transfer from the excited donors (sensitizers) to the ground state acceptors.…”
Section: Resultssupporting
confidence: 80%
“…These values can be compared with an expected slope of À0.178 mol kJ À1 for reactions involving complete electron transfer. [36][37][38] The plots shown in Fig. 4, using our measured values of the half wave oxidation potentials and triplet energies of the substituted naphthalenes reported recently by Schmidt et al, 16 show far less scatter than those reported previously by ourselves.…”
Section: Resultssupporting
confidence: 48%
“…3. That the point for CFCl, falls far off the line et al (15) for the quenching of triplet acetone by olefins and is not surprising since widely divergent values for E A of this -6 eV-' given by Saperstein and Levin (5) for the quenching molecule are given in the literature (5, 13, 14). It is also of singlet aromatics by chloroform.…”
Section: Resultsmentioning
confidence: 71%